ANALISIS PENGARUH KEGUNAAN YANG DIRASAKAN, KEMUDAHAN PENGGUNAAN DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING (Studi pada situs jual beli online Zalora.co.id) - Noviatun, Rosep Tika; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2017)
High growth of technology and consumer’s shifting behavior who want an easy transaction, faster, and efficient cause online business growth that called e-commerce. This causes competition of e-commerce in high temper. Company needs to make their consumers being loyal to their product so they can survive. Between the atmosphere of the competitiveness nowadays, Zalora is one of the most popular e-commerce company in Indonesia that not coupled with the reputation and page viewers to transact in this site. This study was to examine the effect od variabel perceived usefulness, easy of use, and consumer trust on purchase decision of Zalora in Semarang through consumer intention as an intervening variabel.The total sample in this study is 100 respondents taken by purposive sampling technique that comsumers in Semarang and also conduct transaction at least 1 times in Zalora. Data analysis method used are in which the analysis : validity, reliability, classic assumption test, multiple linear regeression, t0test, F-test, determination test and Sobel test.This result of multiple regression analysis showed that all independent variabels are perceived usefulness (0,252). Ease of use (0,625), and customer’s trust (0,165) has a positive and significant relationship to variabel purchase intention. Intervening variabel such as purchase intention (0,625) and independent variabel such as costomer’s trust (0,165) has a positive relationship and parallel to the dependant variabel is purchase intention.